Ground-based optical detection of atmospheric waves in the upper mesosphere and lower thermosphere. - Drob, Douglas Patrick (1996)
Internal waves and atmospheric tides, which propagate into the upper mesosphere and lower thermosphere, are the natural response of the atmosphere to perturbations such as cumulus convection, flow over topography, and solar heating. Seasonal and local time trends have been studied by observing the terrestrial $\rm OH(X\sp2Π )$ and $\rm O(\sp1S)$ airglow layers at the University of Michigan, Peach Mountain Airglow Observatory $\rm (43\sp° N,\ 83\sp° W).$ Using a Michelson interferometer, OH(3,1) band intensities and neutral temperature at 89 km have been measured. Simultaneously, a Fabry-Perot interferometer was used to measure the zonal and meridional wind velocities at 89 km and 97 km. In addition, an all-sky CCD camera was used to measure the spatial morphology of airglow perturbations. This work is important to the field because it presents the first long term multi-instrument observation of the $\rm OH(X\sp2Π )$ airglow. Additionally, eighty continuous hours of observations were made in mid-January, 1991 at Thule Air Base, Greenland $\rm (76.3\sp° N,\ 68.5\sp° W)$ using simliar observation techniques. In agreement with recent theory, analysis indicates semi-annual seasonal fluctuations in the OH(3,1) number density and annual fluctuations in temperature. Average local time fluctuations were compared to the Global Scale Wave Model (GSWM) of Hagan et al. (1995) and the Horizontal Wind Model (HWM93) of Hedin et al. (1993) to investigate the seasonal trends in tidal modulation. The data indicates that a strong semi-diurnal tide (12-hr) dominates the region in the winter months, while other months show equal contributions from both the diurnal (24-hr) and semi-diurnal tides. Spectral analysis of the high-latitude observations shows that coherent tidal oscillations were present in the region. A climatological study of wave activity at three scales was also conducted; short period gravity waves ($<$ 1 hr), long period gravity waves and inertio-gravity waves (1-24 hr), and planetary waves ...